Gudi guday ki shadi - Rashid, Muhammad; Sajid Qureshi (Feroz sons Karachi, 2003)
A whimsical tale about a child's imaginative play, "Gudi Guday Ki Shaadi" follows the enchanting journey of two dolls as they prepare for their grand wedding. This heartwarming story celebrates childhood innocence, creativity, and the power of imagination.